Chemical composition and antibacterial activity of Ageratina neriifolia (B.L.Rob.)(Asteraeae) extracts from Mérida-Venezuela - Ustáriz, María Eugenia Lucena de; Fajardo, Francisco Javier Ustáriz; Briceño, Karina Meza; Fermín, Luís Beltrán Rojas-; Carrero, Verónica Soto; Rojas, Yndra Elena Cordero de; Rodríguez, Silvia Hipatia Torres; Lucena, Javier Ernesto Ustáriz (Emirates Journal of Food and Agriculture, 2021)
This work’s main objective was to chemically characterize and determine the antibacterial activity of the extracts from fresh leaves of Ageratina neriifolia (Asteraceae) collected at the La Culata area in the State of Mérida in Venezuela. The extracts obtained via cold maceration with hexane and dichloromethane were concentrated under reduced pressure on a rotary evaporator and later analyzed by gas chromatography coupled with mass spectrometry (GC-MS). The identification of the components was carried out by comparison of their mass spectra. The evaluation of the extracts’ antibacterial activity was carried out employing the agar-disk diffusion test against gram-positive and gram-negative strains. Sixteen (16) compounds were identified in each extract, corresponding to 75.03% (hexane) and 68.32% (dichloromethane) of the total of isolated compounds. The main components in the hexane and dichloromethane extracts were kaureno-19-acetate (24.48% and 18.41%, respectively) and kaurenol (10.46% and 11.22%, respectively). The results showed that the hexane extract showed not to be soluble in dimethylsulfoxide, so it was not possible to determine the antibacterial activity under the experimental conditions established in the study. While, the dichloromethane extract exhibited activity against the gram-positive bacteria (Staphylococcus aureus and Enterococcus faecalis) and against the gram-negative bacteria (Pseudomona aeruginosa), at a Minimum Inhibitory Concentration (MIC) of 156, 625, and 2.500 µg / mL, respectively. Results that show the antibacterial activity of Ageratina neriifolia hexane extract against gram-positive and gram-negative bacterial strains, unlike that previously described for other species of the genus Ageratina.